From Here to Eternity in the Prayers of Saint Christopher and their Manuscript Variations. - Thomson, S. C. (Parergon, 2024)
The article presents the discussion on early medieval hagiographers used Saint Christopher's cynocephalic physicality to illustrate the transcendence of prayer and its unifying power across time and communities. Topics include role of Saint Christopher's unique physical traits in his narrative, the interaction between scribes and the prayers in manuscripts; and the varied responses and adaptations of these prayers by medieval readers.